A comparison of occupational accidents in the manufacturing and construction sector through data mining techniques - Polo Barrera, Clodoaldo; Martínez-Rojas, María; Rubio-Romero, Juan Carlos (My University, 2021)
This study tries to analyze the most common causes and the variables with the greatest influence on the occurrence of occupational accidents in Spain. Specifically, it focuses on the two sectors with the highest incidence rate in oc- cupational accidents in our country, the construction and the manufacturing sec- tors. The objective of this study is to find out what relationships exist between the accidents that occur in both sectors, trying to find similarities and differences. These relationships may be useful to understand them and to be able to take more effective actions in order to prevent accidents in the future. To address the mentioned objective, a database provided by the Ministry of Labor and Social Economy, which contains all the accidents registered in the Delt@ system of the ministry from 2009 to 2018 has been used. After exploring the database, several variables have been analyzed with the data mining technique of decision trees. Throughout the study, obtained results provide useful information for both sectors and might be useful for decision-makers when making decisions.
Keywords: Accidentes de trabajo; Construcción -- Medidas de seguridad; Occupational accidents; Health and Safety; Information Systems; Construction Sector; Manufacturing Sector; KNIME platform